The study of economic development indicators affecting the performance evaluation of private banks in Syria using factor analysis (applied study on two banks: Bank Bimo Saudi French and Bank Syria and Overseas). (Journal of Hama University, 2025)
The researcher aims to study and analyze the economic development indicators and performance indicators of private banks in Syria in order to reach the most important performance variables and the indicators affecting them using factor analysis, in addition to trying to find the nature of the relationship between the performance variables of private banks and the economic development indicators affecting them in Syria by relying on the data published by the Central Bureau of Statistics and the periodic reports of the Central Bank of Syria and the studied banks for a time series between (2010-2020). The results of the study showed that the performance variables of private banks can be reduced from 6 variables to 2 basic factors, and the variables of economic development indicators affecting the performance of these banks can also be reduced from 8 variables to 2 basic factors, in addition to finding through studying the relationship between the performance variables of private banks and the economic development indicators affecting them using the multiple regression model that there is a significant impact of economic development indicators on all the studied performance variables of private banks.
Keywords: factor analysis; performance of private banks; economic development indicators.